Design e ergonomia na divulgação da ciência e a questão dos museus para a alfabetização científica: o caso do Museo Galileo - Mello, Débora Amaral Taveira (2020)
Science museums have demonstrated over time through academic research an encouraging environment to awaken the desire to learn more about scientific content, bringing artifacts and concepts closer to visitors in a different way than any other media can offer. This research took place at the Museo Galileo in Florence, Italy. There, we sought to investigate how the public interacts with exhibitions in two rooms from a qualitative perspective, despite the existence of quantitative data: "The New World of Galileo" and the first room in the Interactive Area of the Museum. This field study was divided into three parts: the first consists of a non-participatory observational phase, analyzing how visitors behave in the room where the notable artifacts and studies by Galileo Galilei are found. In this stage, data were collected from 203 people and their actions. From these data, it was possible to direct the second phase of the research to one of the rooms in the Interactive Area, in which data were collected from 210 visitors and how they interacted with the models available at the exhibition, this research was also observational and non-participatory. With these data, it was possible to understand the need for further studies on two exposed models that did not allow interaction: the models that presented the Eudoxus’ System and the Ptolemy’s System. The second phase consisted of interviews involving 22 visitors, analyzing their understanding of the models. Finally, a modification is proposed according to aspects of ergonomic design. This serves as a reflection for those who intend to develop scientific models or to design exhibitions.